MgO:LiNbO3 Nonlinear Wavelength Converters - From Visible to Mid-Infrared - Sun, Jian (My University, 2014)
Annealed proton-exchanged (APE) MgO:PPLN ridge waveguides have been successfully developed, and its optical properties have been researched. Nonlinear wavelength conversion experiments have been successfully conducted using the developed waveguide. The APE MgO:PPLN ridge waveguide has been proved suitable for high efficiency nonlinear optical conversions across its transparency spectrum from visible to mid-IR light. With distinctive features including flexibility, high efficiency and low cost, this new type of waveguide can find potential applications in various application fields.
Keywords: Lithium Niobate; Waveguide